Code-Switching in Podcast: A Case Study of Boy William and Cinta Laura (Universitas Terbuka, 2024)
In Indonesian society, code switching has become a popular communication method among celebrities. In addition to being a simple means of expressing specific ideas, some speakers find that code-switching facilitates more natural communication. This study aims to examine the various code-switching techniques used by Boy William in his podcast with Cinta Laura. They employ code switching in their conversation, which will be the primary focus of this study. Specifically, it will investigate the variety of code-switching techniques used in Boy William and Cinta Laura's exchange and how each user employs them when conversing. A quantitative descriptive method is employed in this study. This study's findings demonstrate four different forms of code switching. Nine code switching data were discovered during the study, including two inter-sentential, two intra-sentential, three emblematic, and two establishing continuities with the previous speaker data. The code switching is happened to highlight the utterance, explaining the information, and giving examples.